The COPD Biomarker Qualification Consortium (CBQC). (1st June 2013) - Casaburi, Richard; Celli, Bartolome; Crapo, James; Criner, Gerard; Croxton, Thomas; Gaw, Alasdair; Jones, Paul; Kline-Leidy, Nancy; Lomas, David A.; Merrill, Debora; Polkey, Michael; Rennard, Stephen; et al.
Abstract: Knowledge about the pathogenesis and pathophysiology of chronic obstructive pulmonary disease (COPD) has advanced dramatically over the last 30 years. Unfortunately, this has had little impact in terms of new treatments. Over the same time frame, only one new class of medication for COPD has been introduced. Even worse, the rate at which new treatments are being developed is slowing. The development of new tools for the assessment of new treatments has not kept pace with understanding of the disease. In part, this is because drug development tools require a regulatory review, and no interested party has been in a position to undertake such a process. In order to facilitate the development of novel tools to assess new treatments, the Food and Drug Administration, in collaboration with the COPD Foundation, the National Heart Lung and Blood Institute and scientists from the pharmaceutical industry and academia conducted a workshop to survey the available information that could contribute to new tools. Based on this, a collaborative project, the COPD Biomarkers Qualification Consortium, was initiated. The Consortium in now actively preparing integrated data sets from existing resources that can address the problem of drug development tools for COPD.